To Play or Not to Play : Corrosion of Historic Brass Instruments - Skamletz, Martin; von Steiger, Adrian (2023)
The present volume brings together the results of a multidisciplinary research project on corrosion inside historical brass instruments. In this SNSF-funded project Brass Instruments Between Preventive Conservation and Use in Historically Informed Performance, the Hochschule der Künste Bern collaborated with the Swiss National Museum, the Paul Scherrer Institute, the Institute for Building Materiales at ETH and Klingendes Museum Bern, among others. The results - here complemented with further contributions on the topic of conservation of brass instruments, especially in museum settings - have been presented at the Fourth International Romantic Brass Symposium (2017), organised together with the International Committee for Museums and Collections of Instruments and Music (CIMCIM). Musicological and organological questions meet chemical and physical analyses, which in turn are considered in terms of their manageability and practical relevance in the museum context.